Joint maintenance and controller reconfiguration policy for a gradually deteriorating control system. (August 2017) - Langeron, Yves; Grall, Antoine; Barros, Anne
This paper tackles the maintenance decision-making of gradually deteriorating control systems. The main feature of these systems is their ability within a closed-loop to drive actuators in order to set the controlled process in a given state. Usually, the existing literature deals with the diagnosis of faults of a control system and the means to recover system performances after their appearance. The controller reconfiguration is one of these means. The root cause of a fault is rarely argued nor its occurrence time. Before designing maintenance policies, this paper proposes a stochastic modeling framework of a degrading control system focusing on the actuator deterioration. It is based on the assumption of a close relationship between the controller setting, the actuator deterioration and finally its faulty situations. These latter are related to given degradation thresholds. Due to the stochastic nature of the deterioration, the thresholds hitting times are random. The obtained model allows the conditional reliability of the actuator to be assessed and then the prognosis of its residual useful life (RUL). This RUL is finally used to achieve two maintenance policies based upon the reconfiguration of the controller which is therefore considered as a new maintenance action.